Assessment of Residential Satisfaction using Importance-Performance Analysis: A Case Study in Naypyitaw City, Myanmar - Phyu, Pan Ei; Effendi, Nursyirwan; Purnawan, Purnawan (Jurnal Teknik Sipil dan Perencanaan, 2024)
This study evaluates the residential satisfaction of government-provided four-storey apartment buildings within civil-servant housing in Naypyitaw City, Myanmar. The research is based on a questionnaire survey conducted in nine civil-servant housing complexes situated in Naypyitaw's residential zone. Its primary objective is to identify key attributes that can enhance residents' satisfaction with these apartment buildings and provide recommendations for future housing development. Utilizing a multi-cluster sampling method and employing face-to-face interviews, respondents rated attribute importance and satisfaction using a five-point Likert Scale. The collected data were subjected to Importance-Performance Analysis (IPA), revealing ten priority attributes for improving residential satisfaction. These findings suggest that enhancing residents' contentment involves modifying and reviewing factors such as Ceiling Height, Layout Plan of Apartment, Size of Rooms and Corridor, Numbers of Rooms, Staircase Design, and addressing Neighborhood Relations. Additionally, the study underscores the importance of situating housing near essential amenities like Schools for Children, Shopping Locations, Places of Worship, and Police Stations to create a more livable city.